Intermaxillary fixation as co-adjuvant treatment for morbid obesity - Vassimon, H. S.; Pigoli, D. R.; Viterbo, Fausto [UNESP]; Palhares Neto, Aristides Augusto [UNESP]; Haddad, ALM; Padovani, Carlos Roberto [UNESP]; Mazzoni, A.; Nogueira, Célia Regina [UNESP] (F D-communications Inc, 2004)
Background: the effective long-term treatments for morbid obesity is bariatric surgery. However, the associated surgical and anesthetic risks led the authors to evaluate intermaxillary fixation, a less aggressive procedure, as a preoperative treatment in selected patients with morid obesity.Methods: 22 patients (5 male, 17 female, ages 16-53 years, with BMI 44.9 +/- 5.4 kg/m(2)) underwent intermaxillary fixation. The procedure consisted of fitting brackets on the front face of the teeth and posterior application of elastic bands to impede mouth opening.Results: At the end of 6 weeks, weight loss was 7.4 +/- 2.6% there was general improvement in lipid profile, glycemia, and blood pressure. There was no recorded discomfort, pain, or any other difficulty during this treatment.Conclusion: Intermaxillary fixation can be used as a pre-surgical solution for weight reduction in preparation for bariatric surgery, improving co-morbid aspects such as blood pressure, glycemia, and lipid profile.
Keywords: intermaxillary fixation; morbid obesity; co-morbidities; bariatric surgery; dental treatment; weight loss